2011
DOI: 10.11646/zoosymposia.6.1.17
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Spirotetramat toxicity to immatures and sublethal effects on fecundity of female adults of </strong><strong><em>Tetranychus urticae </em></strong><strong>Koch*</strong></p>

Abstract: Acute toxicity of spirotetramat to immatures and its sublethal effects on adult females of two-spotted spider mite, Tetranychus urticae Koch, were investigated in laboratory bioassays, at 27 ± 2°C, 50–80% RH and 16/8 L/D photoperiod.Acute toxicity was tested by successive treatments of eggs, larvae, protonymphs and deutonymphs on bean leaf discs, and mortality was evaluated based on the number of mites reaching the adult stage. Concentration-mortality data were subjected to probit analysis and the following LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Gong et al (2016) and Ramalakshmi et al (2020) revealed that spirotetramat was highly effective on the A. gossypii fecundity and increased the total CarE activity dramatically. At the same pace, the insecticidal effect of spirotetramat was confirmed against other insects, cotton mealybug, Phenacoccus solenopsis (Rezk et al, 2019 andSequeira et al, 2020), Tetranychus urticae Koch (Marcic et al, 2011 andSaryazdi et al, 2013). Fiaz et al (2018) found that combined application of spirotetramat along with Isaria fumosorosea formulation has shown a significant synergistic effect against Diaphorina citri infestation.…”
Section: Discussionmentioning
confidence: 88%
“…Gong et al (2016) and Ramalakshmi et al (2020) revealed that spirotetramat was highly effective on the A. gossypii fecundity and increased the total CarE activity dramatically. At the same pace, the insecticidal effect of spirotetramat was confirmed against other insects, cotton mealybug, Phenacoccus solenopsis (Rezk et al, 2019 andSequeira et al, 2020), Tetranychus urticae Koch (Marcic et al, 2011 andSaryazdi et al, 2013). Fiaz et al (2018) found that combined application of spirotetramat along with Isaria fumosorosea formulation has shown a significant synergistic effect against Diaphorina citri infestation.…”
Section: Discussionmentioning
confidence: 88%
“…Pyflubumide is classified in the new subgroup 25B (carboxanilide) in the IRAC (Insecticide Resistance Action Committee) MoA classification as a novel inhibitor of mitochondrial complex II on the respiratory chain and has a similar mechanism to cyenopyrafen and cyflumetofen, so resistance to this compound may have developed via the same factors [ 39 , 40 ]. Spirodiclofen, spiromesifen, and spirotetramat have sterility effects on adult females and ovicidal effects on eggs but do not have a control effect on adults [ 41 ]. Therefore, abamectin, acequinocyl, bifenazate, and fluxametamide will be effective in controlling adults that have developed resistance to etoxazole and pyridaben.…”
Section: Discussionmentioning
confidence: 99%